Multiband Fractal Antenna Design and Characterisation Using Antenna Miniaturization Techniques - Singh, Rajveer (My University, 2012)
Modern telecommunication system requires antennas with wider bandwidth and smaller dimensions than conventional antennas. Operators are looking for systems that can perform over several frequency bands. This has initiated antenna research in various directions, one of which is by using fractal shaped antenna elements. The types of functionality now being demanded includes multiband operation, in some cases different radiation patterns are needed in the different bands. For example, the handsets are being produced with terrestrial cellular capability coupled with satellite based communications along with Bluetooth, Wi-Fi, GPS and many other operations. Fractal plays a prominent role for these requirements. Fractal antenna uses a geometric shape that has the property of self-similarity. Fractal antennas have ability to add more electrical length in less volume. Fractal antennas have improved impedance, improved SWR (standing wave ratio) performance on a reduced physical area, when compared to non-fractal Euclidean geometries. Fractal antennas show compressed resonant behaviour. In many cases, the use of fractal element antennas can simplify circuit design. Often fractal antennas do not require any matching components to achieve multiband or broadband performance. The aim of this thesis is to design multiband antennas with circular patch and triangular antennas for wireless communication systems and study the effect of iterations and changing shape of straight triangles to curved triangles. Here, coaxial feed method is used to excite the patch antennas. This thesis presents a design of circular patch four triangles and five triangles antennas. The triangles shapes are changed to get new antennas like straight and curved antennas. The proposed design of antennas have been modelled, designed and simulated using Computer Simulation Technology (CST) Microwave Studio 2010. These designs include the base design on circular patch and 4 to 5 triangles. The triangles are straight and curved. Other antennas are obtained by iterating the base design to different values. The antennas are designed on the FR-4 substrate with ε= 4.3 and thickness 1.4 mm. The designed antennas are studied experimentally for return loss and resonant frequencies behaviour using CST Microwave Studio 2010. The proposed antennas are multiband antennas and small in size. It is found that increase in number of fractal iterations, number of resonant frequencies also increases. Further, this thesis focuses on unique features of fractal geometries along with its applications is different fields. It will be shown that how to quantify the space-filling ability of fractal geometries, and how this correlates with miniaturization. Several examples of fractal antennas which are designed recently are discussed in this thesis.
Keywords: Multiband Fractal Antenna Design; Antenna Miniaturization Techniques